The innovation impact of EU emission trading: findings of company case studies in the German power sector - Karoline S. Rogge; Malte Schneider; Volker H. Hoffmann (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2010)
This paper provides a comprehensive analysis of how the European Emission Trading System (EU ETS) as the core climate policy instrument of the European Union has impacted innovation. Towards this end, we investigate the impact of the EU ETS on research, development, and demonstration (RD&D), adoption, and organizational change. In doing so, we pay particular attention to the rela-tive influences of context factors (policy mix, market factors, public acceptance) as well as firm characteristics (value chain position, technology portfolio, size, vision). Empirically, our analysis is based on multiple case studies with 19 power generators, technology providers, and project developers in the German power sector which we conducted from June 2008 until June 2009. We find that the innovation impact of the EU ETS has remained limited so far because of the scheme's initial lack in stringency and predictability and the relatively greater importance of context factors. Additionally, the impact varies tremendously across technologies, firms, and innovation dimensions, and is most pronounced for RD&D on carbon capture technologies and corporate procedural change. Our analysis suggests that the EU ETS by itself may not provide sufficient incentives for fundamental changes in corporate climate innovation activities at a level adequate for reaching political long-term targets. Based on the study's findings, we derive a set of policy and research recommendations.
urn:nbn:de:0011-n-1191395
Keywords: 330; EU ETS; emission trading; innovation; technological change; adoption; diffusion; organizational change; power sector